Anticoagulation therapy in atrial fibrillation after intracranial hemorrhage - A. S. Gerasimenko; V. S. Gorbatenko; O. V. Shatalova; V. I. Petrov (Столичная издательская компания, 2021)
Intracerebral hemorrhage (ICH) is severe and fatal complication of anticoagulant therapy with an incidence 0.3-0.7% per year. For patients with atrial fibrillation (AF) anticoagulants are administered for decreasing risk of stroke and systemic embolism. In this case the occurrence of intracranial bleeding is hard task for doctor. From the one side it is necessary to reverse the action of the drug for preventing the growth of hematoma. At the same time the discontinuation of therapy increases the risk of systemic embolism for patients with AF significantly. Clinical guidelines and studies have been reviewed about ICH during anticoagulant therapy. Nowadays there is no quality evidence about reversal of anticoagulant effects after ICH and optimal time of resumption of anticoagulant therapy. Firstly, we do not have large randomized controlled trials on this issue. The majority of clinical guidelines were based on retrospective studies and opinions of experts. Soon several randomized controlled trials will be finished and new data will be presented.